Alkyne gem‐Hydrogenation: Formation of Pianostool Ruthenium Carbene Complexes and Analysis of Their Chemical Character. Issue 26 (17th May 2019) - Biberger, Tobias; Gordon, Christopher P.; Leutzsch, Markus; Peil, Sebastian; Guthertz, Alexandre; Copéret, Christophe; Fürstner, Alois
Abstract: Parahydrogen ( p ‐H2 ) induced polarization (PHIP) NMR spectroscopy showed that [Cp X Ru] complexes with greatly different electronic properties invariably engage propargyl alcohol derivatives into gem ‐hydrogenation with formation of pianostool ruthenium carbenes; in so doing, less electron rich Cp X rings lower the barriers, stabilize the resulting complexes and hence provide opportunities for harnessing genuine carbene reactivity. The chemical character of the resulting ruthenium complexes was studied by DFT‐assisted analysis of the chemical shift tensors determined by solid‐state 13 C NMR spectroscopy. The combined experimental and computational data draw the portrait of a family of ruthenium carbenes that amalgamate purely electrophilic behavior with characteristics more befitting metathesis‐active Grubbs‐type catalysts. Abstract : Portrayal : Less electron‐donating cyclopentadienyl (Cp X ) ligands lower the barrier for the perplexing gem ‐hydrogenation of alkynes by [Cp X Ru] complexes and kinetically stabilize the resulting pianostool ruthenium carbenes. The chemical shift tensors extracted from solid state 13 C NMR spectra draw a portrait of electrophilic carbenes of the Fischer‐type with a certain flavor reminiscent of Grubbs catalysts.